PENGARUH KUALITAS, DESAIN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KERAMIK PLATINUM DI WRINGINANOM GRESIK - Susantik, Susantik; Mulyati, Awin; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2017)
The purpose of this study was to determine and analyze the influence of Quality (X1), Design (X2) and Price (X3) Buying Decision Against Ceramic Products Platinum. This research was conducted in the District of Wringinanom, Gresik in East Java because the object of this study is that consumers ceramics Platinum. The sampling technique used was purposive sample to use the formula to obtain the 100 respondents, the analysis method used is data analysis quantitative use test data quality, classic assumption test, multiple linear regression and statistical tests that use independent variables Quality Products (X1), Design (X2), Price (X3) and the dependent variable purchase decision (Y). The results of this study, the value of regression is Y = 5.455 + 0.240 + 0.231 X1 + 0.229 X2 X3 + e. Based on statistical data analysis, indicators in this study are valid and are reliable variables. In the classic assumption test, normally distributed, do not have a problem multicoloniarity, heteroskedastisitas not happen, and there is no autocorrelation. The third independent variable Product Quality (X1), Design (X2), Price (X3) significantly influence the purchase decision dependent variable (Y). Testing R2 test (test of determination) values obtained in Adjusted R square of 0.267, or 26.7% of purchase decisions are determined by the ceramic products Platinum Quality (X1), Design (X2), and Price (X3). While 73.3% are influenced by other factors which are not included in this regression model.Â Keywords: Product Quality, Design, Price, Purchase Decision